Новые данные о морфологии Thominx tritonispunctati comb. n. (Nematoda, Capillariidae) — паразита хвостатых амфибий - Ломакин, В.В. (Вестник зоологии, 1982)
A detailed redescription f ThominxtrilonispunctaliD i e s i n g .1851), comb. n, an intestinal parasite of Merlensiella caucasica, with special reterence to oral and caudal
body end structures, bacillar stripe stichosome, reproductive system etc. On the ground or obtained morphological data, the species is assigned to the genus Thominx D u i a r
d i n , 1845.